Buyer Attraction Strategy: The Role of Quality and Design in the Cibaduyut Leather Shoe Industry - Praptika Jaya, Adi; Johan, Ahmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study aims to analyze the influence of product quality and product design on consumer purchasing decisions of shoes in Cibaduyut. Product quality that includes aspects of durability, comfort, and materials used, and attractive and innovative product design are considered the main factors that influence consumer preferences in choosing shoes. This study uses a quantitative method with data collection techniques through questionnaires distributed to shoe consumers in Cibaduyut. The data obtained were analyzed using a linear regression test to determine the extent to which product quality and product design influence purchasing decisions. The results of the study indicate that product quality and product design have a positive and significant influence on purchasing decisions. Consumers are more likely to choose shoes that have high quality and attractive designs according to fashion trends. Therefore, business actors in Cibaduyut need to continue to improve product quality and innovate in design to meet consumer preferences and increase competitiveness in the market.